Against Eurocentrism : a Transcendant Critique of Modernist Science, Society and Morals. - Kanth, Rajani Kannepalli (Palgrave Macmillan, 2006)
This book renders an uncompromising verdict on the 'scourge' of our millennium: modernism, itself the artifact of certain late Eurocentric propensities. Kanth argues that while modernism is possessed of some virtues, they are purchased at far too high a cost--indeed a cost that neither the species nor the planet can, on any scale, find affordable. Given the imminence and the gravity of this threat, he further suggests that no other posture is at all ecologically responsible. We must, Kanth suggests, break with the manifold paradigms of European expansionism or find ourselves, soon enough, livi.